Health-related Knowledge Development in Roma Pupils - Jozef Liba (Ignatianum University Press, 2017)
The paper discusses possible ways of systematic implementation of intervention programs designed for the development of health-related knowledge and skills in Romany pupils. The research results indicate a considerable educational potential of a health education intervention program pursuing substantial increase in healthrelated knowledge in Romany primary school pupils. The results suggest that pro-health programs integrated in school curricula are a relevant part of health-oriented education of Romany pupils.